Occurrence of mcr-1 and mcr-2 colistin resistance genes in porcine Escherichia coli isolates (2010–2020) and genomic characterization of mcr-2-positive E. coli - Ewers, Christa; Göpel, Lisa; Prenger-Berninghoff, Ellen; Semmler, Torsten; Kerner, Katharina; Bauerfeind, Rolf (Frontiers in Microbiology, 2022)
The global emergence of plasmid-mediated colistin resistance is threatening the efficacy of colistin as one of the last treatment options against multi-drug resistant Gram-negative bacteria. To date, ten mcr-genes (mcr-1 to mcr-10) were reported. While mcr-1 has disseminated globally, the occurrence of mcr-2 was reported scarcely. We determined the occurrence of mcr-1 and mcr-2 genes among Escherichia coli isolates from swine and performed detailed genomic characterization of mcr-2-positive strains. In the years 2010-2017, 7,614 porcine E. coli isolates were obtained from fecal swine samples in Europe and isolates carrying at least one of the virulence associated genes predicting Shiga toxin producing E. coli (STEC), enterotoxigenic E. coli (ETEC) or enteropathogenic E. coli (EPEC) were stored. 793 (10.4%) of these isolates carried the mcr-1 gene. Of 1,477 additional E. coli isolates obtained from sheep blood agar containing 4 mg/L colistin between 2018-2020, 36 (2.4%) isolates were mcr-1-positive. In contrast to mcr-1, the mcr-2 gene occurred at a very low frequency (0.13%) among the overall 9,091 isolates. Most mcr-2-positive isolates originated from Belgium (n=9), one from Spain and two from Germany. They were obtained from six different farms and revealed multilocus sequence types ST10, ST29, ST93, ST100, ST3057 and ST5786. While the originally described mcr-2.1 was predominant, we also detected a new mcr-2 variant in two isolates from Belgium, which was termed mcr-2.8. MCR-2 isolates were mostly classified as ETEC or ETEC-like, while one isolate from Spain represented an atypical enteropathogenic E. coli (aEPEC; eae+). The ST29-aEPEC isolate carried mcr-2 on the chromosome. Another eight isolates carried their mcr-2 gene on IncX4 plasmids that resembled the pKP37-BE MCR-2 plasmid originally described in Belgium in 2015. Three ST100 E. coli isolates from a single farm in Belgium carried the mcr-2.1 gene on a 47-kb self-transmissible IncP type plasmid of a new IncP-1 clade. This is the first report of mcr-2 genes in E. coli isolates from Germany. The detection of a new mcr-2 allele and a novel plasmid backbone suggests the presence of so far undetected mcr-2 variants and mobilizable vehicles.